PERAN ORANGTUA TERHADAP PEMELIHARAAN KESEHATAN GIGI DAN MULUT ANAK DAN STATUS KESEHATAN GIGI DAN MULUT ANAK KELAS II SD MEDAN : PARENT’S ROLE OF DENTAL ORAL HEALTH CARE AND DENTAL HEALTH STATUS OF THE SECOND GRADE STUDENT IN MEDAN - Lina Natamiharja; Margaret (Dentika: Dental Journal, 2011)
The main problem of dental care in children mouth not only in developed countries but also in developing countries. According to Household Health Survey in 2004 the prevalence of caries in Indonesia up to 90,05 %. This research was done to know parents role in taking care dental health of children, the dental health status and the relation between parents role with the dental health status. The type of this research is cross sectional study. The samples of this research were students and their parents. The numbers of sample were 167 students. Data sampling of children’s dental health status was being done by direct examination of oral cavity by using debris index according to Greene and Vermillion, deft index according to Klein and gingivitis index according to Ramfjord. Meanwhile data of parent’s role was being done by giving questionaires. The result of this research showed that father’s roles was still less in teaching their children how to brush teeth since 2 years old, notifying the time to brush teeth, accompanying children to dentist and checking oral health, yet there were well in taking care of children in brushing teeth till now, providing the toothbrush and toothpaste which is suitable for children and in taking care of the eating habits of children, while mother’s role was not much different. The mean of deft index of children was 4,20 ± 3,25, OHIS 0,39 ± 0,55 and gingivitis 0,03 ± 0,06. The result of the research showed that was relation between parent’s role with the mean of deft index, OHIS index and gingivitis index in children. In conclusion, the parents’ role in taking care of children’s dental health could affect the dental health status in children.